Effectiveness of Micro Credit Management in Minimized Non-Performing Loans at Bank BJB - Denny Mulyadi; Kiki Yulia Nurul Ramadhani; Haris Resmawan (Sean Institute, 2025)
This study was motivated by the high ratio of non-performing loans (NPL) in Bank BJB’s Micro Credit product, which once reached 34%, far above the Bank Indonesia threshold. The research aims to analyze the effectiveness of Bank BJB’s credit management in minimizing bad loans, identify their causes, and explore handling strategies. The study employed a descriptive quantitative method with a case study approach. The population consisted of 185 microcredit debtors, with 65 respondents selected through simple random sampling. Data were collected through field studies, literature reviews, questionnaires, and interviews, and analyzed using validity and reliability tests, simple linear regression, correlation, coefficient of determination, and t-test. The findings reveal that credit management effectiveness significantly influences bad loan minimization with a contribution of 28.1%, while 71.9% is affected by external factors. The better the implementation of planning, credit procedures, 5C and 7P analyses, interest rate determination, and credit supervision, the stronger the bank’s ability to control credit risk. The study concludes that effective credit management is a crucial instrument in maintaining banking health. It is recommended that Bank BJB enhance human resource competence, strengthen supervision, and develop adaptive risk mitigation strategies to external conditions.